Immunogenicity of the Conjugate Meningococcal ACWY-TT Vaccine in Children and Adolescents Living with HIV - Arantxa Berzosa; Sara Guillen; Cristina Epalza; Luis Escosa; Maria Luisa Navarro; Luis M. Prieto; Talía Sainz; Santiago Jimenez de Ory; Marina Montes; Raquel Abad; Julio A. Vázquez; Irene Serrano García; et al. (Microorganisms, 2023)
Background: Children and adolescents living with HIV (CALHIV) are at high risk of meningococcal infections and may present lower immune responses to vaccines. The objectives of this study were to assess the immunogenicity of the quadrivalent Men ACWY-TT vaccine (Nimenrix®) in CALHIV after a two-dose schedule and to describe possible HIV-related factors that may affect the immunogenic response. Methods: A multicenter prospective study was designed, including CALHIV followed in five hospitals in Madrid, between 2019 and 2021. Two doses of the Men ACWY-TT vaccine were administered. Serum bactericidal antibody (SBA) assays using rabbit complement (rSBA) against serogroups C, W, and Y were used to determine seroprotection and vaccine response (the proportion achieving a putative protective titer of ≥eight or a ≥four-fold rise in titer from baseline). Serum was collected at baseline, and at 3 and 12 months after vaccination. Results: There were 29 CALHIV included, 76% of whom were perinatally infected. All were receiving TAR and presented a good immunovirological and clinical status overall. At baseline, 45% of CALHIV had seroprotective titers to at least one serogroup, with individual seroprotection rates of 24%, 28%, and 32% against C, W, and Y, respectively. After a two-dose schedule, vaccine response was 83% for each serogroup, eliciting a vaccine response to all serogroups in 69% of them. One year after vaccination, 75% of CALHIV maintained seroprotective titers against the C serogroup, and 96% against W and Y. None of the HIV-related characteristics analyzed could predict vaccine response or antibody duration. Conclusions: CALHIV who received effective TAR and presented a good immuno-virological situation achieved an appropriate vaccine response after two doses of the Men ACWY-TT vaccine, and antibody-mediated protection against serogroups C, W, and Y was maintained in more than 70% of the patients one year after vaccination.